2009
DOI: 10.1097/01.pra.0000358315.88931.fc
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Depression

Abstract: TT may have an antidepressant effect in depressed patients, especially those with hypogonadism or HIV/AIDS and elderly subpopulations. The route by which TT is administered may play a role in treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(93 citation statements)
references
References 123 publications
2
83
1
2
Order By: Relevance
“…This confirms the results of previous studies which showed that therapeutic interventions to address the endocrine dysfunction also help to ameliorate depression (16,17,19). A meta-analysis also confirms the positive effect of testosterone on depressed patients and in subpopulations with hypogonadism and HIV (20).…”
Section: Discussionsupporting
confidence: 78%
“…This confirms the results of previous studies which showed that therapeutic interventions to address the endocrine dysfunction also help to ameliorate depression (16,17,19). A meta-analysis also confirms the positive effect of testosterone on depressed patients and in subpopulations with hypogonadism and HIV (20).…”
Section: Discussionsupporting
confidence: 78%
“…Although women produce less androgen hormone than men and metabolize a higher proportion of their androgen to oestrogen, direct androgen activity mediated via the AR influences development of the female phenotype and is important for the healthy functioning of multiple organs in women, including the ovaries (Lebbe & Woodruff 2013, O'Reilly et al 2014, Sen et al 2014, uterus (Wood et al 2009, Cloke & Christian 2012, bone (Watts et al 1995), muscle (Smith et al 2014), adipose tissue (Barbosa-Desongles et al 2013, Chazenbalk et al 2013, and brain (Shifren 2002, Lobo et al 2003, Ryan et al 2009, Zarrouf et al 2009). However, less is known about the mechanisms of AR signalling in female tissues compared with either AR signalling in male target tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Но благоприятное дей-ствие на когнитивные функции, согласно результа-там исследований, было менее выраженным [74,75]. Следовательно, целесообразность проведения тера-пии тестостероном можно обсуждать после исклю-чения других причин когнитивных нарушений [76].…”
Section: благоприятные эффекты леченияunclassified